Immune response to cytosolic DNA via intercellular receptor modulation in oral keratinocytes and fibroblasts. (30th November 2020) - Naruse, Takako; Ohta, Kouji; Kato, Hiroki; Ishida, Yoko; Shigeishi, Hideo; Sakuma, Miyuki; Fukui, Akiko; Nakagawa, Takayuki; Tobiume, Kei; Nishi, Hiromi; Takechi, Masaaki
Abstract: Objective: Double‐strand (ds) DNA‐enveloped viruses can cause oral infection. Our aim is to investigate whether oral mucosal cells participate in immune response against cytosolic dsDNA invasion. Methods: We examined the response to transfected herpes simplex virus (HSV) dsDNA via intracellular receptors in oral keratinocytes (RT7) and fibroblasts (GT1), and the effect of TNF‐α on those responses. Results: Transfected dsDNA increased CXCL10 expression via NF‐κB activation in both cell types, while those responses were inhibited by knockdown of RIG‐I, an RNA sensor. Although IFI16, a DNA sensor, was expressed in the nuclei of both types, its knockdown decreased transfected dsDNA‐induced CXCL10 expression in GT1 but not RT7 cells. IFI16 in GT1 cells was translocated into cytoplasm from nuclei, which was attributed to immune response to cytosolic dsDNA. TNF‐α enhanced transfected dsDNA‐induced CXCL10, and knockdown of IFI16 decreased TNF‐α and dsDNA‐driven CXCL10 expression in both RT7 and GT1 cells. Finally, the combination of TNF‐α and transfected dsDNA resulted in translocation of IFI16 from nuclei to cytoplasm in RT7 cells. Conclusion: RIG‐I and IFI16 in oral mucosal cells may play important roles in host immune response against DNA viral infection, while TNF‐α contributes to development of an antiviral system via those intracellular receptors.